A highly efficient reusable homogeneous copper catalyst for the selective aerobic oxygenation sulfides to sulfoxides. Issue 11 (14th March 2018) - Ren, Cheng; Fang, Runxing; Yu, Xiaochun; Wang, Shun
Graphical abstract: Highlights: CuSO4 acts a reusable homogeneous catalyst. Molecular oxygen as the green oxidant. Mild reaction conditions. High conversion and high selectivity. Abstract: Readily available copper showed efficient activity and great selectivity for the homogeneous catalysis of oxidation of sulfides to sulfoxides using molecular oxygen as the oxidant. The reaction proceeds under mild conditions in the presence of a catalytic amount of TEMPO. Importantly, the catalysts could be conveniently recovered and reused. And this methodology was proved to be applicable for the transformation of various aromatic and aliphatic sulfides into the corresponding sulfoxides with high conversion and high selectivity.